2017
DOI: 10.5812/rijm.12021
|View full text |Cite
|
Sign up to set email alerts
|

Confirmatory Factor Analysis of Persian Version of Depression, Anxiety and Stress (DASS-42): Non-Clinical Sample

Abstract: Background: Based on historical viewpoint, relationship among depression, anxiety and stress attracted clinical and theoretical consideration. Despite the relative overlap of these psychological disorders in general, these three syndromes are distinctive in terms of theoretically and conceptually aspects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…Thus, the DASS-21 was found to concurrently measure depression and anxiety simultaneously and distinctively among the respondents. These concurrent coefficient values were also similar to other findings of other workers from other countries (Mahmoud et al, 2010;Ramli et al, 2011;Osman et al, 2012;Le et al, 2017;Haibi et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, the DASS-21 was found to concurrently measure depression and anxiety simultaneously and distinctively among the respondents. These concurrent coefficient values were also similar to other findings of other workers from other countries (Mahmoud et al, 2010;Ramli et al, 2011;Osman et al, 2012;Le et al, 2017;Haibi et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Since its design, DASS has been widely used as a screening instrument to measure symptoms of stress, anxiety and depression in clinical settings (Lovibond & Lovibond, 1995a;Lovibond and Lovibond, 1995b). The DASS has been translated to different languages and used in many validation studies and it was found to be Indexed African Journals Online: www.ajol.info psychometrically sound (Mahmoud et al, 2010;Hashim et al, 2011;Haibi et al, 2017). The DASS also has an advantage over other psychometric instruments in that it does not only screen for psychopathology; it assists towards diagnoses of depression, anxiety and stress (Mahmoud et al, 2010;Hashim et al, 2011;Haibi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown high concurrent validity for Beck Depression Inventory, Beck Anxiety Inventory, and DASS. Also, this tool can detect stress symptoms from depression and anxiety (23). Comparing the results from DASS-21 with the diagnosis of psychiatric interviews showed the sensitivity and specificity of 75% to 89% for this tool and its potential for accurate screening of depression, anxiety, and stress (24, 25).…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, noise pollution is one of the factors affecting the quality of life around the world 14,34 . According to the World One of the valid scales for measuring the main symptoms of depression, anxiety and stress is the DASS scale, which is a set of three self-reporting scales for assessing negative emotional states in depression, anxiety and stress 11,21,32 . Due to the nature of the work, the steel industry has a high level of noise, and according to studies conducted in third world countries, there is more concern about the severity of industrial noise and its consequences 2 .…”
Section: Introductionmentioning
confidence: 99%